Innovation For Making Herbal Beverages As An Effort To Fight The Covid19 Virus In The Community Of Senden Village, Kediri Regency - Susilaturochman Hendrawan K; Garnika Ade Sinto Raya; Arif Kustoro; Budi Hantoro; Imam Sugeng; Imam Suhaimi; Stevanus Gatot Supriyadi (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
Corona virus is a virus thatcan infect the respiratory system. One of the effort to prevent corona virus infection is to increase the body’s immune status. In a effort to protect themselves from this virus, many people are starting to look at supplements to strengthen their immune system. The assumption that supplements can prevent the corona virus is not entirely true. Supplements can indeed provide us with the nutritional intake needed to support health and endurance. However, this does not necessarily prevent direct transmission of the virus. The solution and one of the local wisdoms of the people in Indonesia in increasing immunity is the habit of consuming herbal drinks which are believed to increase the body’s immunity because there are several very useful ingredients. The purpose of this PKM activity is as one of the preventive measure taken by the people of Senden village, Kediri Regency in warding off the corona virus/covid-19 by making innovations in herbal drinks from processed spices and consuming herbal drinks as an effort to ward off the corona virus or covid19. This activity uses training methods and direct assistance throught the preparation and implementation stages of making herbal drinks.